(untitled) (Jurnal Manajemen Bisnis, 2025)
This study set out to explore how four financial ratios—DAR (Debt to Asset Ratio), DER (Debt to Equity Ratio), ROA (Return on Assets), and ROE (Return on Equity)—influence the value of banking businesses listed on the Indonesia Stock Exchange (IDX). Using a quantitative method, researchers analyzed the financial statements of IDX-listed companies in the financial sector through multiple linear regression. To ensure the reliability of the regression model, it was tested for normality, multicollinearity, heteroscedasticity, and autocorrelation using classical assumption tests. However, the results showed that none of the four variables—DAR, DER, ROA, or ROE—had a significant impact on firm value, either individually or collectively. This was confirmed by both the F-test and the t-test. The model’s R² value was just 0.014, meaning these variables explain only 1.4% of the changes in firm value. The remaining 98.6% is likely influenced by other factors outside the scope of this study. In short, this research suggests that DAR, DER, ROA, and ROE may not be the most useful indicators for assessing the value of financial sector companies. Future studies should consider additional variables, such as broader economic conditions and internal management strategies, to gain deeper insights into what drives firm value in this industry.